Pengaruh Dana Pihak Ketiga (DPK) dan Biaya Operasional Pendapatan Operasional (BOPO) terhadap Return On Asset (ROA) (Studi Kasus Pada Bank Umum Swasta Nasional Devisa yang Terdaftar di BEI) - Astuti, Wati Aris; Hardi, Marisa (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2015)
This study aims to determine the development of the Third Party Funds, thedevelopment of Operating Expenses to Operating Income and the development ofReturn on Assets, as well as to determine whether the Third Party Funds significantlyinfluence whether the Return on Assets and Operating Expenses Operating Incomesignificantly affects the Return On Asset. The population used in this study is theForeign Exchange Commercial Banks listed in Indonesia Stock Exchange. The sampleused is the annual financial statement of the balance sheet and income statement ofthe 6 banks 2008-2013. The sample using purposive sampling method. The method used in thisresearch is descriptive and verification methods. The test statistic used is multiplelinear regression analysis, hypothesis testing with the help of application program IBMSPSS 20.0.The results showed that the Third Party Funds significantly influence the Returnon Assets and Operating Expenses to Operating Income significantly influence theReturn on Assets at the Foreign Exchange Commercial Banks listed in Indonesia StockExchange.